Effects of Multidimensional Social Exclusion on Child Well-Being: An Examination of Migration Paradox in Chinese Children. - Jiang, Shan; Wang, Lin; Jiang, Chaoxin; Tan, Shilin (Journal of Child & Family Studies, 2024)
Although associations between social exclusion and child well-being were previously identified, how they varied by migration status remained unclear. The present study aims to extend prior research by examining the "migration paradox" in a sample of Chinese children. Data were collected in Kunming, China, using a multi-stage cluster random sampling. The sample consisted of 1322 Chinese children (36.6% migrants) aged 8–17 years old (M = 11.80 years; SD = 1.56). Structural equation modeling (SEM) with multi-group analysis was adopted to examine the mediating effect of socio-relational exclusion between structural-economic exclusion and child well-being, and the moderating effect of migration status. The results revealed that structural-economic exclusion increased socio-relational exclusion, which in turn, negatively related to child well-being. Multi-group SEM indicated that the effects of structural-economic exclusion and socio-relational exclusion were stronger for urban local children than for migrant children. These findings underscored the importance of reducing social exclusion among children in social work interventions and social policies. Highlights: This research aims to extend prior research by examining the "migration paradox" in a sample of Chinese children. Migrant children reported a higher level of deprivation and relational exclusion and a lower level of social participation and well-being compared with local urban children. The effects of social exclusion on child well-being were stronger for urban local children than for migrant children.